A severe adrenal crisis occurred in late diagnosed Sheehan’s syndrome developed in a 17-year-old woman - Ozkan Sevencan, Nurhayat; Erem Basmaz, Seda; Ertinmaz Ozkan, Aysegul; Kayhan, Burcak (Annals of Medical Research, 2021)
None